Manjapuik Barokah Ramadhan: Enhancing Qur'anic Literacy And Ibadah Practices In Sago Salido Village Through Service Learning - Tumanggor, Ilham; Hasibuan, Muhammad Syarif Muda; Muhartrisia, Yurahmi; Dongoran, Irham (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented to enhance Qur'anic literacy and strengthen ibadah practices among the community around Jabal Rahmah Mosque and Rumah Tahfiz Qur'an (RTQ) Ibnu Mas'ud, Nagari Sago Salido, Pesisir Selatan Regency, West Sumatra, through a Service Learning approach. The "Manjapuik Barokah" themed program involved 41 participants, 30 congregational mothers, and 11 RTQ students, using participatory and educational methods over 15 days during Ramadan. The Service Learning stages encompassed preparation (needs identification), service (implementation of tahsin halaqah, practical fiqh workshops, and religious social activities), reflection (student-community evaluation and reflection), and celebration (program closure and sustainability). Evaluation results demonstrated significant improvements in Qur'anic reading abilities, with 80% of students experiencing increased memorization of at least ¼ juz, 25% improvement in mothers' tajwid reading quality. They strengthened ukhuwah Islamiyah through religious social activities. Students acquired experiential learning experiences that enhanced pedagogical and leadership competencies through systematic reflection. This program successfully established a sustainable community-based religious education system involving local halaqah coordinators. The Service Learning approach effectively bridges academic theory with real community needs while developing student character through critical reflection processes.